Design and Implementation of a Web Based Health Information System (International Journal of Technology and Management Research, 2020)
Health Information System aims at improving and enhancing the delivery of quality, data availability and administrative effectiveness of people’s health. Medical record has come under severe threat as a result of the manual system of medical record keeping in spite of its important functions. This system of record-keeping involves taking down patient data on pieces of paper, which are put into files and kept in cabinets. In fact, this is an improper means of documentation resulting in loss and mismatch of patient data, and time wastage. It is alsocumbersome, bulky and consumes a lot of the office space. In this paper, a complete web-based health information system is designed to solve these problems so as to enable users handle details on policies efficiently and effectively. A test of the system over various network topologies reveals that time taken to move a packet and received acknowledgment for standalone, LAN, WAN and Intranet is 3ms, 4ms, 8ms and 10ms respectively. These short periods of time show faster and efficient delivery of health activities. The Web Based HealthInformation System thus provides significant benefit to institutions as it can capture data and store it in the developed database for future use.Citation: Kwasi, T. M., Patrick, A.A, Amponsah Wellington, A. Design and Implementation of a Web-BasedHealth Information System, 2020; 5(3): 1－11.Received: August 4, 2019Accepted: September 30, 2020
Keywords: Health information system; MySQL; Hospital Management; system development life cycle